Analisis Profil Dasar Saluran Untuk Mengurangi Kecepatan Aliran Pada Pengalihan Sungai - Dinar Dwi Anugerah Putranto; Agus Lestar Yuono; MA Muzakki Effendi (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2020)
In coal mining activities, it is often found that coal reserves are located in layers far from the land surface, and can be located far below the riverbed. In such conditions, the choice that is often taken is to move the river flow. Displacement of river flows in accordance with the regulations allowed has its own challenges to minimize the risks that will occur to the environment. The aim of the study is to design the basis of a new channel to reduce the speed of the river flow, so that the function and sustainability of river use as an ecological function is not disturbed. The method used is to analyze the origin of the river channel discharge and design the dimensions of the diversion river channel. The results obtained, with forecasts of a 50 year return peak flood period of 104.17 m3 / sec and with a divergence in the elevation of the diverting river channel of 18.9 m between the planned upstream and downstream along the 6,212.7 m, then to avoid massive scouring at channel base, a maximum flow rate of 10 m / sec and a minimum of 0.8 m / sec with a channel bottom of 0.0005% is recommended. For this reason the base profile of the canal is trapped at a distance of 500 m, with an elevation difference of 0.25 m. To maintain ecological sustainability, the dimension of the diversion river channel is maintained the same as the original river, b = 8m, H = 3.5m, and H : V = 1.5: 1.